(untitled) (Research, Society and Development, 2020)
The Brazilian obstetric scenario is characteristically marked by the excess of interventions and the disregard for the parturient’s role, violating the human right to safe and humane care during labor. This study aimed to reveal the experience of parturition in maternity hospitals in Campina Grande / PB in the users’ perception. This is a study with a qualitative approach developed in the Basic Health Units with a sample of 17 women, approached through interviews guided by a semi-structured script. The data were analyzed in the Thematic Content Analysis modality, anchored in the theoretical framework of the scientific literature and the guidelines that conceptualize and guide the debate on obstetric violence, emerging two empirical categories: Loneliness versus exposure during parturition and The faces of obstetric violence. The results showed that most women reported the absence of health professionals during parturition, and when they were present, they promoted mistreatment with the performance of unnecessary interventionist techniques and psychological abuse. Furthermore, women experienced during hospitalization the absence of pain management during childbirth and exposure of their bodies for learning purposes or the lack of an adequate physical structure, resulting in a traumatic experience. All of these findings point to the absence of dignified care, and to the need for professional qualification for humanized assistance.